Study on Interfacial Shear Properties of Concrete Reinforced Stone Arch Bridges Using Staad.pro A Review - Hanwate, Tirangini; Gupta, Sandeep; Jain, Supriya (International Journal of Scientific Research in Civil Engineering, 2021)
Bridges are the structural components that are required for the efficient movement of Trains and locomotives and under earth embankment for crossing of water course like streams across the embankment as road embankment cannot be allowed to obstruct the natural water way. Bridges can be of different shapes such as arch, slab and box. These can be constructed with different material such as masonry (brick, stone etc.) or reinforced cement concrete. Since bridge pass through the earthen embankment, these are subjected to same traffic loads as the road carries and therefore, required to be designed for such loads. The cushion depends on rail profile at the bridge location. For analysis relevant IRCs are required to be referred. The structural elements are required to be designed to withstand maximum bending moment and shear force. In this study we are reviewing latest researches and publications on analysis of bridge structures, stone bridges and vehicular loading conditions.
Keywords: Analysis; Bridge; Staad.Pro; IRC; Structure; Forces; Displacement; Stone Masonry